2015
DOI: 10.5194/gmdd-8-2403-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancement for bitwise identical reproducibility of Earth system modeling on the C-Coupler platform

Abstract: Abstract. Reliable numerical simulation plays a critical role in climate change study. The reliability includes bitwise identical reproducibility, i.e. bitwise identical result of numerical simulation can be reproduced. It is important to Earth system modeling and has already been used intra modeling groups for the model development. However, it is rarely considered in a wider range even worldwide. To help achieve the worldwide bitwise identical reproducibility, we introduce the detailed implementations for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…First a bilinear interpolation is carried out on the two horizontal levels, followed by a vertical interpolation. Bitwise reproducibility of the simulation results has been verified [ Liu et al ., ].…”
Section: Model Descriptionsmentioning
confidence: 99%
“…First a bilinear interpolation is carried out on the two horizontal levels, followed by a vertical interpolation. Bitwise reproducibility of the simulation results has been verified [ Liu et al ., ].…”
Section: Model Descriptionsmentioning
confidence: 99%
“…Song et al (2012) and Hong et al (2013) investigated the uncertainty due to the round-off error in climate simulations. Liu et al (2015a, b) discussed the importance of bitwise identical reproducibility in climate models.…”
Section: Introductionmentioning
confidence: 99%
“…One may think it is easy to update compiling setups, just by installing new compiler version or changing compiler flags. However, it is challenging to update compiling setups for Earth system modeling, because researchers may get significantly different results from the same experiment when using different compiling setups (Liu et al, 2015b). A compiler not only translates the code in a high-level programming language to a low-level language but also tries to improve computational performance of the codes with compiler optimization schemes.…”
Section: Introductionmentioning
confidence: 99%
“…The first challenge concerns reproducibility of simulation results. Due to the chaotic nature of the climate system, more and more studies have shown that trivial round-off errors can trigger significant changes in simulation results of Earth system modeling (Hong et al, 2013;Liu et al, 2015b;Song et al, 2012). Due to the differences of performance optimization schemes among different compiling setups, a change of compiling setups potentially introduces round-off errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation